STEAM-Based PjBL Learning During The COVID-19 Pandemic - Fauziah, Intan Risfi; Sapriya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The world of education is one of the fundamental sectors affected by the COVID-19 pandemic. With the implementation of social distancing, the learning system that was originally face-to-face becomes online (in a network). The existence of a learning system from home or distance learning experiences various kinds of obstacles. Learning is not optimal due to limited access to teaching and learning. The selection of the right learning model is one of the keys to overcoming these obstacles. STEAM learning (Science, Technology, Engineering, Arts, and Mathematics) integrated with project-based learning (PjBL) is an alternative to online learning that has characteristics in line with teaching and learning situations and conditions that are dominated by the use of information and communication technology. The research method used is descriptive qualitative with a quantitative approach. The subjects in this study were students in the sixth grade of elementary school, as many as 30 people. The data was collected using observation and documentation techniques and then analyzed qualitatively and quantitatively related to the achievement of students objectively. The results showed that 74.1% of PjBL's integrated STEAM learning achievements were in the